In Vitro Screening of a 1280 FDA-Approved Drugs Library against Multidrug-Resistant and Extensively Drug-Resistant Bacteria - Lucie Peyclit; Sophie Alexandra Baron; Linda Hadjadj; Jean-Marc Rolain (MDPI AG, 2022)
Alternative strategies against multidrug-resistant (MDR) bacterial infections are suggested to clinicians, such as drug repurposing, which uses rapidly available and marketed drugs. We gathered a collection of MDR bacteria from our hospital and performed a phenotypic high-throughput screening with a 1280 FDA-approved drug library. We used two Gram positive (Enterococcus faecium P5014 and Staphylococcus aureus P1943) and six Gram negative (Acinetobacter baumannii P1887, Klebsiella pneumoniae P9495, Pseudomonas aeruginosa P6540, Burkholderia multivorans P6539, Pandoraea nosoerga P8103, and Escherichia coli DSM105182 as the reference and control strain). The selected MDR strain panel carried resistance genes or displayed phenotypic resistance to last-line therapies such as carbapenems, vancomycin, or colistin. A total of 107 compounds from nine therapeutic classes inhibited >90% of the growth of the selected Gram negative and Gram positive bacteria at a drug concentration set at 10 µmol/L, and 7.5% were anticancer drugs. The common hit was the antiseptic chlorhexidine. The activity of niclosamide, carmofur, and auranofin was found against the selected methicillin-resistant S. aureus. Zidovudine was effective against colistin-resistant E. coli and carbapenem-resistant K. pneumoniae. Trifluridine, an antiviral, was effective against E. faecium. Deferoxamine mesylate inhibited the growth of XDR P. nosoerga. Drug repurposing by an in vitro screening of a drug library is a promising approach to identify effective drugs for specific bacteria.